Developing Students' Artistic Creativity Through Local Wisdom-Based Project Learning - Ifrianti, Syofnidah; Hasnanto, Anton Tri; Yuslinda, Amelia Febi (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the effectiveness of the Local-Wisdom-Based Project-Based Learning (PjBL) model in enhancing elementary students’ creativity in collage art. Motivated by the low creativity observed in art-based learning, the research applied a quantitative quasi-experimental method with a Nonequivalent Control Group Design. The study involved 59 fourth-grade students at SD Negeri 1 Tanjung Gading Bandar Lampung, split into an experimental group using Local-Wisdom-Based PjBL and a control group taught through the Group Investigation (GI) model. Creativity was assessed using a validated instrument covering fluency, flexibility, originality, and elaboration, administered through pretest and posttest. Results showed significant improvement in creativity for both groups, with the experimental group showing higher effectiveness (N-Gain = 59.06) compared to the control group (N-Gain = 44.26). The Independent Samples t-test confirmed a significant difference in posttest results (t = 3.745, p = .000), demonstrating that Local-Wisdom-Based PjBL was more effective than the GI model in fostering creativity. These findings align with previous research and highlight that integrating cultural identity, such as Lampung siger, can enhance creative expression. The study suggests that culturally contextualized PjBL can strengthen 21st-century competencies and cultural awareness in elementary art education. Future research should examine larger sample contexts and long-term effects for broader applicability.